WATERSHED APPROACH IN TERRITORIAL MANAGEMENT AT THE LOCAL LEVEL - Berezhnyi, Vitaliy (Human Geography Journal, 2015)
Article integrates the concepts about the watershed approach, territorial management and the use of GIS tools in the system of environmental management at the local level. A brief retrospective review of the use of the watershed approach in applied geography is presented. Advantages of the approach in solving the problems of natural resources are discussed. Attention is focused on a number of assumptions that justify the importance of the approach in environmental management at the local level. Some aspects of the use of GIS for the implementation of the approach in the territorial management are considered.